Feral Futures, or The Animal That Therefore I Am Not (Less to Follow) - Andres Matlock (The Before and the After: Critical Asynchrony Now, 2025)
Taking its cue from Derrida’s “The Animal That Therefore I Am (More to Follow),” this chapter considers the dynamic origins and ends of plants. By reading ancient arguments for natural teleology in Cicero and Theophrastus alongside contemporary ecological accounts of feral activity, I outline a critical history of the entanglement between human and non-human agency. From the perspective of the feral future, the human ability to shape the growth of plant life only works from within the vegetal forces that transform us in turn.